Laminin heparin-binding peptides bind to several growth factors and enhance diabetic wound healing - Ishihara,J; Ishihara,A; Fukunaga,K; Sasaki,K; White,MJV; Briquez,PS; Hubbell,JA (Nature Communications, 2018)
Laminin, as a key component of the basement membrane extracellular matrix (ECM), regulates tissue morphogenesis. Here, we show that multiple laminin isoforms promiscuously bind to growth factors (GFs) with high affinity, through their heparin-binding domains (HBDs) located in the α chain laminin-type G (LG) domains. These domains also bind to syndecan cell-surface receptors, promoting attachment of fibroblasts and endothelial cells. We explore the application of these multifunctional laminin HBDs in wound healing in the type-2 diabetic mouse. We demonstrate that covalent incorporation of laminin HBDs into fibrin matrices improves retention of GFs and significantly enhances the efficacy of vascular endothelial cell growth factor (VEGF-A165) and platelet-derived growth factor (PDGF-BB) in promoting wound healing in vivo, under conditions where the GFs alone in fibrin are inefficacious. This laminin HBD peptide may be clinically useful by improving biomaterial matrices as both GF reservoirs and cell scaffolds, leading to effective tissue regeneration.